Implications of New Standards on Technical Diagnostics and Control Implementation for the Gas Transmission System Efficiency - Karpash, M.O.; Oliynyk, A.P.; Kogut, G.M.; Klyun, A.M. (Наука та інновації, 2019)
Introduction. Ukrainian gas transmision system (GTS) as a part of the whole oil and gas complex takes the important
role in energy security of the state. Taking into consideration the aging and physical deterioration procesess, a lot of attentionn
today is paid to the question of ensuring GTS relaible operation and maintenance.
Problem Statement. All innovations and technicaogical achievements, implemented into GTS are impossible without a
detailed study of productivity of GTS facilities, the costs for implementing the new standards, and the costs for eliminating
the emergency situations’ consequences.
Purpose. Assessment and evaluation of data on efficiency of Ukrainian GTS, based on the implementation of new standards
on technical diagnostics and control (TDC), influencing significantly on the operation of GTS facilities.
Materials and Methods. For the analysis, we chose the complex mathematical model, allowing to determine the qualitative
relationship between the productivity of GTS facilities, the costs of implementing new standards for technical diagnostics
and control, and the costs for eliminating the consequences of economic, environmental and other impacts. Besides
the expert evaluation method and numerical Runge-Kutt methods were applied for practical use of the proposed model.
Results. The efficiency of GTS operation, according to the proposed model, depends on the costs, spent for the implementation
of standards. Among the benefits for increasing of standards expenditures are the growth of emergency response
funding, which tends to decreasing in timely manner. Calculation results showed the adequacy of the proposed experts’
assessment model according to the question of objectivity, impartiality and consistency of expert opinions.
Conclusions. The complex of mathematical calculations maintained the qualitative picture of the relationship between
selected characteristics. The new approach to analysing data on Ukrainian GTS efficiencywas suggeted, presenting the
mechanism for establishing the dependencies between costs of implementing new standards and costs for eliminating
emergency situations. Вступ. Українська газотранспортна система (ГТС), як складова всього нафтогазового комплексу, відіграє важливу роль у енергетичній безпеці держави. Питання забезпечення роботи та технічного обслуговування ГТС, враховуючи процеси старіння та фізичного зносу системи, насьогодні є актуальними.
Проблематика. Всі нововведення та технологічні досягнення, впроваджені в ГТС, неможливі без детального
вивчення питань продуктивності об'єктів ГТС, витрат на впровадження нових стандартів, а також витрат на усунення
наслідків надзвичайних ситуацій.
Мета. Оцінювання та аналіз даних щодо ефективності роботи української ГТС через впровадження стандартів
з технічного діагностування і контролю (ТДК), що суттєво впливає на функціонування елементів ГТС.
Матеріали і методи. Для аналізу обрано математичну модель, що дозволяє визначити якісну залежність між
продуктивністю об'єктів ГТС, витратами на впровадження нових стандартів з ТДК та витратами на усунення
на с лідків економічного, екологічного та іншого характеру. Для оцінки практичного використання запропонованої
мо делі застосовано методи експертного оцінювання та чисельні методи Рунге-Кутта.
Результати. Ефективність роботи ГТС, відповідно до наведеної моделі, залежить також від витрат на впровадження стандартів. Серед переваг підвищення видатків на стандарти є зростання обсягів фінансування на випадок
надзвичайних ситуацій, що має тенденцію до зменшення у часі. Результати розрахунку показали адекватність запропонованої моделі експертного оцінювання щодо об'єктивності, неупередженості та узгодженості думок експертів.
Висновки. Застосування комплексної математичної моделі дозволяє отримати якісну картину взаємозв'язків
між обраними характеристиками. Запропоновано новий підхід до аналізу даних щодо ефективності української ГТС
через застосування механізму внесення нових залежностей між затратами на впровадження нових стандартів та
затратами на ліквідацію можливих аварійних ситуацій. Введение. Украинская газотранспортная система (ГТС), как составляющая всего нефтегазового комплекса,
играет важную роль в энергетической безопасности государства. Вопрос обеспечения работы и технического обслуживания ГТС, учитывая процессы старения и физического износа системы, на сегодняшний день актуальны.
Проблематика. Все нововведения и технологические достижения, внедренные в ГТС, невозможны без детального
изучения вопросов производительности объектов ГТС, затрат на внедрение новых стандартов, а также расходов на
устранение последствий чрезвычайных ситуаций.
Цель. Оценка и анализ данных об эффективности работы украинской ГТС через внедрение стандартов по
техническому диагностированию и контроля (ТДК), что существенно влияет на функционирование элементов ГТС.
Материалы и методы. Для анализа использовали математическую модель, позволяющую определить качественную зависимость между производительностью объектов ГТС, затратами на внедрение новых стандартов ТДК и
расходами на устранение последствий экономического, экологического и иного характера. Для оценки практического использования предложенной модели применены методы экспертного оценивания и численные методы Рунге-Кутта.
Результаты. Эффективность работы ГТС, согласно приведенной модели, зависит от затрат на внедрение стандартов. Среди преимуществ повышения расходов на стандарты является рост объемов финансирования на случай
чрезвычайных ситуаций, имеющий тенденцию к уменьшению во времени. Результаты расчета показали адекватность
предложенной модели экспертной оценки объективности, беспристрастности и согласованности мнений экспертов.
Выводы. Применение комплексной математической модели позволяет получить качественную картину взаимосвязей между избранными характеристиками. Предложен новый подход к анализу данных об эффективности украинской ГТС путем применения механизма внесения новых зависимостей между затратами на внедрение новых стандартов и затратами на ликвидацию возможных аварийных ситуаций.